Measuring emotional well-being through subjective report: a scoping review of reviews - Jessica B Koslouski; Christine D Wilson-Mendenhall; Parisa Parsafar; Simon Goldberg; Michelle Y Martin; Sandra M Chafouleas (BMJ Open)
Objective This scoping review of reviews aims to describe the current landscape of measures of emotional well-being (EWB).Methods Following established practices for scoping reviews, we searched the PsycInfo, ERIC, Scopus and PubMed databases in June and July 2021 for reviews of measures of EWB that described their review methods and psychometric properties of included measures. From each eligible article, two coders independently extracted the authors’ (1) definition of EWB, (2) purpose for the review, (3) methods (eg, search terms, inclusion and exclusion criteria), (4) identified measures (including any noted adaptations) and (5) the scope of psychometric information presented. Descriptive and content analyses were used to examine data.Results Forty-nine reviews were included in this scoping review. Reviews included anywhere between 1 and 34 measures of EWB and 135 unique EWB measures were captured across all reviews. We found that there was no consistent definition of EWB, identified measures varied widely and reviews were published in a range of disciplines. Psychometric evidence varied as did authors’ purposes for conducting the reviews.Conclusions Overall, these reviews suggest that literature on EWB measurement is disjointed and diffuse. Conceptual integration and harmonisation of measures is needed to advance knowledge of EWB and its measurement.Trial registration numbers 10.17605/OSF.IO/BQDS7 and 10.17605/OSF.IO/WV8PF.